Vitro / 2 - Khoury, Jessica, 1990- (The Corpus Files, 2015)
"On a remote island in the Pacific, Corpus scientists have taken test tube embryos and given them life. These beings--the Vitros--have knowledge and abilities most humans can only dream of. But they also have one enormous flaw"--